The potential for automating assisted natural regeneration of tropical forest ecosystems - Elliott S. (2017)
© 2016 The Association for Tropical Biology and Conservation Assisted (or accelerated) natural regeneration (ANR) will play an important role in meeting the UN target to restore forest to 350 million hectares of degraded land, by 2030. However, since most accessible land is already used for agriculture, most of the sites, available for ANR, are far from roads and/or on difficult terrain, where implementing ANR with human labour is not practical. Therefore, this paper explores the potential of emerging technologies, such as low-cost UAVs (drones) and new imaging devices, to automate ANR tasks, including site monitoring (to assess site potential for natural regeneration, plan interventions and assess progress), maintenance of natural regeneration (particularly weeding) and species enrichment through aerial seeding. The usefulness of existing technologies is reviewed and future innovations needed, to provide practicable support for ANR, are discussed. Intensive collaboration, among technologists and forest ecologists, will be essential to ensure that technological innovations are based firmly on sound restoration science.